Preventive Medicine between Obligation and Aspiration - Verweij, M.F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2000)
Preventive Medicine between Obligation and Aspiration is a study of ethical questions regarding mass screening, vaccination, and health policy programmes. These interventions aim to enhance public health but may also constrain personal autonomy and cause harm, and influence our moral views. So far, these issues have hardly been subject to systematic ethical analysis. This study aims to fill this gap by providing an overview of moral problems in preventive medicine and by explicating norms for good practice. Throughout the book it is argued that some moral concerns about prevention - namely concerns about medicalization - cannot be adequately grasped in terms of strict and binding moral norms. Various moral concepts and types of norms `beyond obligation' are explored and developed in order to give practical meaning to these rather vague concerns. In this way the book contributes to applied ethics as well as to ethical theory. It is of interest to professionals in public health and preventive medicine and to scholars in applied ethics and moral philosophy.
1 Introduction -- I: Preventive Medicine: Moral Problems and Moral Norms -- 2 What is preventive medicine? -- 3 Medical-ethical dimensions of preventive medicine -- 4 The prevention paradox and tensions between private and public interests -- 5 Medicalization as a moral problem for preventive Medicine -- II Obligation and Beyond -- 6 The concept of duty and obligation -- 7 Medicalization, moral obligations and beyond -- 8 Beyond obligation -- 9 Conclusions.
Keywords: Public health; Ontology; Ethics; Public Health; Ontology; Ethics